Negócios processuais aplicados às ações de despejo, no âmbito das locações urbanas - Oliveira, Jackson Rios (2023)
This is a study that seeks to investigate the possibility of changing the procedure for eviction due to lack of ownership, within the scope of urban locations. The inclusion of procedural legal business, disciplined by article 190 and sole paragraph of the Code of Civil Procedure, in eviction actions, aims to meet the fundamental norms of civil procedure by delivering to the jurisdiction, in a reasonable time, a fair and effective decision on the merits . The flexibility in the procedure represents greater effectiveness to the material right discussed, in the lease relations, since the parties, as recipients of the jurisdictional benefit, have an interest in influencing the middle activity. They are, in certain circumstances, more empowered than the judge himself to adopt decisions